Development and Validation of a Risk Score for Prediction of Venous Thromboembolism in Patients With Lung Cancer. (5th March 2020) - Li, Zilun; Zhang, Guolong; Zhang, Mengping; Mei, Jie; Weng, Huiwen; Peng, Zhenwei
This study aimed to develop and validate a risk score for early prediction of venous thromboembolism (VTE) in patients with lung cancer. A total of 827 patients with lung cancer from February 2013 to February 2018 in our hospital were retrospectively analyzed. Demographic and clinicopathological variables independently correlated to VTE were applied to develop the risk score in the development group while examined in the validation group. The regression coefficients of multivariable logistic regression test were applied to assign a risk score system. The incidence of VTE was 12.3%, 12.7%, and 11.8% in all patients, in the development and validation groups, respectively. The 496 patients in the development group were classified into 3 groups: low risk (scores ≤3), moderate risk (scores 4-5), and high risk (scores ≥6). The risk of VTE was significantly and positively related to the risk scores in both development and validation groups. The risk score system aided proper stratification of patients with either high or low risk of VTE in the development and validation groups ( c statistic = 0.819 and 0.827, respectively). This risk score system based on the factors with most significant correlation showed good predictive ability and is potentially useful for predicting VTE in patients with lung cancer. However, it was developed and validated by a retrospective analysis and has significant limitations, and a prospective validation with all the classic variables assessing the thrombotic risk is needed for a solid conclusion.